Genetic analysis of a severe case of Netherton syndrome and application for prenatal testing - Müller, F. B.; Haußer-Siller, Ingrid; Berg, D.; Casper, C.; Maiwald, R.; Jung, A.; Jung, H.; Korge, Bernhard P. (British journal of dermatology, 2002)
Netherton syndrome (NS) is a rare autosomal recessive disease with variable expression. It is defined by a triad of symptoms: congenital ichthyosiform erythroderma, trichorrhexis invaginata and atopy. Recently, genetic linkage has been established to the SPINK5 gene locus on chromosome 5q32 encoding the serine protease inhibitor LEKTI. In this study, we present a recurrent homozygous mononucleotide deletion (153delT) resulting in a severe case of NS exhibiting exfoliative erythroderma with lethal outcome at the age of 4 months and its application in prenatal testing in a subsequent pregnancy of the mother.
Gesehen am 01.04.2021